THE EFFECT OF HARMONIC EXERCISES ACCORDING TO THE DISTRIBUTED METHOD TO LEARN SOME SKILLS ON THE FLOOR MOVEMENT MAT IN ARTISTIC GYMNASTICS (American Journal of Pedagogical and Educational Research, 2023)
The aim of this research is to prepare an educational program using harmonic exercises according to the distributed method to learn some skills on the carpet of floor movements, and to identify the effect of harmonic exercises according to the distributed method to learn some skills on the carpet of floor movements in artistic gymnastics. The researcher used the experimental approach due to its suitability to the nature of the problem. The research community was represented by the players of the Kirkuk breeding team for the cubs (10-12) years, who numbered (12) players, who were chosen by the deliberate method. The control group was randomly drawn by (5) players in each group. The experimental group used harmonic exercises according to the distributed method, and the control group used the program prepared by the trainer. The results were processed statistically using the statistical package (SPSS).The researcher concluded the effectiveness of the educational program using harmonic exercises in learning some skills on the floor movements carpet in artistic gymnastics, and the exercise scheduling (distributed method) had a positive impact on learning some skills on the floor movements carpet in artistic gymnastics by dividing rest times between the exercises used as well as between repetitions, and the necessity of developing coordination abilities at an early age, because the central nervous system is easily affected at this age. The researcher recommended the need to pay attention to harmonious exercises because of their great impact on learning different skills, the importance of focusing on giving harmonic exercises at an early age, and the need to use exercise scheduling methods to organize and arrange exercises in educational units according to sound scientific foundations and to serve their purpose, taking into account the target group. When developing educational programs using harmonic exercises according to the different methods of scheduling the exercise